The Global Circulation of Chinese Materia Medica, 1700-1949 A Microhistory of the Caterpillar Fungus - Lu, Di. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book explores the dissemination of knowledge around Chinese medicinal substances from the eighteenth to twentieth centuries in a global context. The author presents a microhistory of the caterpillar fungus, a natural, medicinal substance initially used by Tibetans no later than the fifteenth century and later assimilated into Chinese materia medica from the eighteenth century onwards. Tracing the transmission of the caterpillar fungus from China to France, Britain, Russia and Japan, the book investigates the tensions that existed between prevailing Chinese knowledge and new European ideas about the caterpillar fungus. Emerging in eighteenth and nineteenth-century Europe, these ideas eventually reached communities of scientists, physicians and other intellectuals in Japan and China. Seeking to examine why the caterpillar fungus engaged the attention of so many scientific communities across the globe, the author offers a transnational perspective on the making of modern European natural history and Chinese materia medica. Di Lu is a historian of medicine and modern science. He studied at the University of Kent and University College London, UK, and served as a Thomas Arthur Arnold Fellow, Dan David Scholar, and Zvi Yavetz Fellow at Tel Aviv University, Israel. His research explores the transnational history of medicine and natural history, with a specific focus on cross-cultural exchanges of medicinal substances and species between East Asia and the West from the eighteenth to twentieth centuries.
1. Introduction -- 2. The Spread of a Sino-Tibetan Marvel -- 3. The Caterpillar Fungus Travels Overseas -- 4. The Caterpillar Fungus Teases -- 5. New Caterpillar Fungus Emerges and Negotiates -- 6. Conclusion.
Keywords: World history; Medicine -- History; China -- History; Science -- History; World History, Global and Transnational History; History of Medicine; History of China; History of Science